Labor-Market Concentration and Labor Compensation - Yue Qiu; Aaron J. Sojourner (Institute of Labor Economics (IZA), 2019)
This paper estimates the effect of labor-market concentration on labor compensation across the U.S. private sector since 2000. We distinguish between concentration in local labor markets versus local product markets, guarding against bias from confounded product-market concentration. Analysis extends beyond wages to rates of employment-based health insurance coverage. Estimates suggest negative effects of labor-market concentration on labor compensation. This comes through both reducing the human-capital level of those in the market and reducing pay conditional on human-capital level. Higher product-market concentration exacerbates and higher unionization rates mitigates these effects.
Keywords: J31; J32; J42; L13; J51; 330; labor-market concentration; monopsony; wages; health insurance; unions